Transbronchial biopsies provide longitudinal evidence for epithelial chimerism in children following sex mismatched lung transplantation. Issue 1 (23rd December 2004) - Spencer, H; Rampling, D; Aurora, P; Bonnet, D; Hart, S L; Jaffé, A
Abstract : Background: Recent reports have shown evidence of host derived parenchymal engraftment in several human allografts including the lung, leading to speculation that stem cell therapy may be useful for lung repair in diseases such as cystic fibrosis (CF). To date, previous studies have looked at single surgical or autopsy specimens and no longitudinal studies have been reported. The aim of this study was to assess whether transbronchial biopsies could be used to study the time course of chimerism following lung transplantation. Methods: Specimens of archived transbronchial lung biopsies from five time points taken for clinical purposes from two boys who had received a sex mismatched heart-lung transplant for end stage CF were examined. Sections were dual stained for cytokeratin (epithelium) and a mixture of leucocyte common antigen and CD68 for inflammatory cells. Co-localisation of cells containing a Y chromosome was confirmed by fluorescent in situ hybridisation. Results: Evidence of chimerism was found in up to 6.6% of epithelial cells in bronchial (median 1.4% (range 0–6.6)) and alveolar (median 3.6% (range 2.3–5.5) tissue without apparent evidence of fusion. This engraftment was seen as early as 3 weeks and remained relatively constant up to 37 months. Conclusions: This study has demonstrated proof of principle for long term chimerism in lung epithelium. Transbronchial biopsies may provide a new method for studying the kinetics of stem cell engraftment in the lung.